Religious Family Environment And The Formation Of Moderate Student Character: An Integrative Review Through Religious Moderation and The Love-Based Curriculum - Arica Yogi Seftiana; Mabruri; Ulfa Adilla; Sri Alfiah; Husnil Mubarok; Baili (Jurnal Ilmu Pendidikan dan Sosial, 2023)
Religious intolerance and character erosion among students continue to challenge Indonesia's pluralistic education system, raising the question of how home-based religiosity and school-based pedagogy may be aligned. This study examines how religious family environments contribute to the formation of moderate student character and how this contribution interfaces with religious moderation and the love-based curriculum (kurikulum berbasis cinta) recently advanced by the Ministry of Religious Affairs. An integrative literature review was conducted on 41 peer-reviewed publications (2019–2025) retrieved from Scopus, DOAJ, Sinta 1–3, and Google Scholar using Boolean strings combining religious family, character education, religious moderation, and love-based curriculum. Articles were screened against pre-registered inclusion criteria, appraised with the CASP qualitative checklist, and synthesised thematically following Braun and Clarke. Inter-coder agreement reached Cohen's κ = 0.86. Three themes emerged. First, daily ritual habituation and parental modelling explain 60–75% of the variance in religiosity, discipline, and pro-social conduct reported across reviewed studies. Second, moderation indicators tolerance, balance, justice appear earlier in children from religious homes than in those receiving moderation only at school, suggesting a sequencing effect. Third, the love-based curriculum extends learning into affective and social domains, but its measured impact is conditional on parental reinforcement and digital literacy. The findings indicate that family religiosity, classroom love-pedagogy, and digital-age literacy operate as a coupled system rather than as independent inputs. Educational policy that strengthens any single component without the others risks producing partial outcomes.